Prevalencia de obesidad posCovid-19 en jóvenes universitarios de Tabasco - Roberto Gil-Domínguez; Blanca E Trejo-Sánchez; Carlos J López-Victorio; Adelma Escobar-Ramírez; José A González-Garrido (Instituto Nacional de Salud Pública, 2023)
No disponible